Interleukin 27 Signaling in Rheumatoid Arthritis Patients: Good or Evil? - Han, Liang; Chen, Zhe; Yu, Kun; Yan, Jiahui; Li, Tingting; Ba, Xin; Lin, Weiji; Huang, Yao; Shen, Pan; Huang, Ying; Qin, Kai; Geng, Yinhong; et al. (Frontiers in Immunology, 2022)
The occurrence and development of rheumatoid arthritis (RA) is regulated by numerous cytokines. Interleukin 27 (IL-27) is a soluble cytokine that exerts biological effects by regulating the Janus tyrosine kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway via the IL-27 receptor. IL-27 is known for its pleiotropic roles in modulating inflammatory responses. Previous studies found that IL-27 levels are elevated in RA blood, synovial fluid, and rheumatoid nodules. Cellular and animal experiments indicated that IL-27 exerts multiple regulatory functions in RA patients via different mechanisms. IL-27 inhibits ectopic-like structure (ELS) formation, CD4+ T helper type 2 (Th2) cells, CD4+ T helper type 17 (Th17) cells and osteoclast differentiation in RA, contributing to alleviating RA. However, IL-27 promotes Th1 cell differentiation, which may exacerbate RA synovitis. Moreover, IL-27 also acts on RA synovial fibroblasts (RA-FLSs) and regulatory T cells (Tregs), but some of its functions are unclear. There is currently insufficient evidence to determine whether IL-27 promotes or relieves RA. Targeting IL-27 signaling in RA treatment should be deliberate based on current knowledge.